Inversor dual de único estágio aplicado ao gerenciamento de energia de um painel fotovoltaico e uma célula a combustível - Garcia, Lucas Sampaio (2015)
Alternative energy sources have for some time attracted great interest in the area of static converter development. This fact is related in greater part to issues such as sustainability and detrimental effects on the natural environment, which all contribute to the viability of this type of energy source. In this context, power electronics performs important tasks making viable the connection of all these kind of clean power sources to the conventional grid and also to the load. From this perspective, a new challenge must be faced which is the development of energy management systems capable of providing intelligent planning and control of appliances in low- and high-power applications. That being so, this Ph.D thesis intends to contribute presenting a novel dual transformerless single-stage current source inverter fed by a proton exchange membrane fuel cell (PEMFC) and a photovoltaic (PV) array. High voltage gain and totally controlled output voltage can be achieved without using dedicated step-up dc dc converters or transformers either. The main feature of this inverter structure is the intelligent power management technique which focuses on the extraction of maximum power from the PV array keeping the PEMFC as an energy storage system. Theoretical analysis is presented and corroborated by experimental results of a laboratory prototype.